2020
DOI: 10.1016/j.resuscitation.2020.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 pandemic on out-of-hospital cardiac arrests: A systematic review

Abstract: Introduction In addition to the directly attributed mortality, COVID-19 is also likely to increase mortality indirectly. In this systematic review, we investigate the direct and indirect effects of COVID-19 on out-of-hospital cardiac arrests. Methods We searched PubMed, BioMedCentral, Embase and the Cochrane Central Register of Controlled Trials for studies comparing out-of-hospital cardiac arrests occurring during the pandemic and a non-pandemic period. Risk of bias wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
74
1
27

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 31 publications
8
74
1
27
Order By: Relevance
“…In contrast to Lombardy, Italy, and Paris, France, where a drastic decrease in OHCA survival rate has been reported, 2 , 3 patient outcomes were maintained during the pandemic study period, similar to findings in the Province of Padua, Northeast Italy, and Bologna, Italy. 9 , 10 Consistent with previous studies, 11 , 12 fewer patients received endotracheal intubation in Osaka City because of changing EMS protocols. Scene times did not differ between periods; however, the response time and hospital arrival time were shorter during the COVID-19 period.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In contrast to Lombardy, Italy, and Paris, France, where a drastic decrease in OHCA survival rate has been reported, 2 , 3 patient outcomes were maintained during the pandemic study period, similar to findings in the Province of Padua, Northeast Italy, and Bologna, Italy. 9 , 10 Consistent with previous studies, 11 , 12 fewer patients received endotracheal intubation in Osaka City because of changing EMS protocols. Scene times did not differ between periods; however, the response time and hospital arrival time were shorter during the COVID-19 period.…”
Section: Discussionsupporting
confidence: 78%
“…These results were in contrast to previously reported data that the response time was longer during the COVID-19 pandemic period. 11 , 12 One possible explanation is traffic reduction owing to the stay home policy. Elmer et al showed there were no differences in the provision of laypersons, AED use, and prehospital return of spontaneous circulation in areas with a low COVID-19 prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…In this edition of Resuscitation, two systematic reviews 1 , 2 and a national Spanish cohort study 3 highlight the alarming impact of the COVID-19 pandemic on the management and outcomes of out-of-hospital cardiac arrest (OHCA). The rapidly increasing literature in this area is highlighted by the difference in the number of identified studies between the two systematic reviews, despite only a small difference in search dates.…”
mentioning
confidence: 99%
“…In some patients, the OHCA may be precipitated by hypoxic respiratory failure. 9 This might also explain, in part, the lower rate of shockable rhythms documented in the pandemic OHCA cohorts 1 , 2 and may also have implications regarding the utility of providing ‘hands only’ bystander CPR in these patients. Additionally, SARS-CoV infection has also been documented to cause myocarditis, 10 arrythmias, 11 and a hyper-coagulable state leading to thrombotic events including cerebral vascular accidents.…”
mentioning
confidence: 99%
See 1 more Smart Citation